Stance, Set, Transference: The Differentiation of Two Modes of Clinical Technique. (April 2022) - Celenza, Andrea
Comparative approaches to psychoanalytic theory are a major source of exposure to different theoretical orientations and clinical technique. However, it is not always clear what the analyst actually does when translating theory into practice. As an attempt at clarification, descriptions are provided of two listening stances or attentional sets that are associated with different modes of analytic listening. These modes reside at a relatively low level of abstraction and are experience-near. The two listening stances are (1) a directed attentional set aimed at the identification of conscious or unconscious repetitious patterns, and (2) a diffuse attentional set receptive to emergent phenomena for the purpose of elaborating unconscious fantasy. These listening modes are combined in everyday practice and usually occur in an oscillating fashion; thus, separation of these listening modes in this discussion is for heuristic purposes. At the same time, these modes are prioritized differently among various theoretical models depending on the analyst's intention and goals. They also can be correlated with different types of transferences, evoking different types of clinical material that correspond to the analyst's goals and/or to phases in treatment. Because these attentional modes are governed by different neurophysiological substrates, it is helpful for analysts to have these modes clearly differentiated in their minds, even though engaging these modes tends to be spontaneous and rapidly oscillating. Two clinical vignettes are provided that illustrate the use of these two modes of listening where one or the other is prioritized.